2018
DOI: 10.21077/ijf.2018.65.1.72074-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of biofloc meal on growth and survival of GIFT tilapia

Abstract: A 60 days indoor growth trial was conducted to study the effect of dietary supplementation of biofloc meal on growth and survival of juvenile GIFT tilapia. Four isonitrogenous and isoenergetic experimental diets (32% crude protein) were prepared using biofloc meal at different inclusion levels viz., 0 (T0), 20 (T1), 30 (T2) and 40% (T3). A commercial diet (T4) was used for comparison. The feeding trial was conducted in 15 nos. of 40 l plastic troughs in triplicate, utilising GIFT tilapias weighing an average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
6
11
0
Order By: Relevance
“…The crude lipid content of the bioflocs found in this study was low, ranging from 0.35-0.92 g/100 g. Nevertheless, the lipid values were in line with previous studies reported by Emerenciano et al [12,14], Anand et al [37], Himaja [41], and Durigon et al [43]. In general, the lipid content in biofloc is usually low, with concentrations ranging from below 0.1 to 2.5 g/100 g [20,22,30,36,58,59].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The crude lipid content of the bioflocs found in this study was low, ranging from 0.35-0.92 g/100 g. Nevertheless, the lipid values were in line with previous studies reported by Emerenciano et al [12,14], Anand et al [37], Himaja [41], and Durigon et al [43]. In general, the lipid content in biofloc is usually low, with concentrations ranging from below 0.1 to 2.5 g/100 g [20,22,30,36,58,59].…”
Section: Discussionsupporting
confidence: 91%
“…Although biofloc meet the nutritional standards for aquaculture feeding, it has to be noted that the protein from biofloc should only be considered as a supplement for dietary proteins [8]. Based on earlier studies, dietary supplementation with biofloc ranging from 4% to 50% can improve growth performance and enhance the immune system of cultured organisms [18,21,36,37,39,42,55]. Therefore, the protein contents of 20 and 24 g/100 g recorded in the present study from the tilapia waste bioflocs, in addition to their superior protein content to shrimp waste bioflocs, suggest that this source be used for dietary protein supplementation in the formulation of fish diets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Composition of mineral premix (Quantity per kg): Magnesium -2,800 mg, Iodine -7.4 mg, Iron -7,400 mg, Copper -1,200 mg, Manganese -11,600 mg, Zinc -9,800 mg, Cobalt chloride -4 mg, Potassium -100 mg, Selenium -4 mg, Calcium carbonate -27.25%, Phosphorous -7.45 mg, Sulphur -0.7 mg, Sodium -6 mg, Calpan -200 mg, Aluminium -1,500 mg and Choline chloride -10,000 mg trough were measured for estimation of growth parameters and feed utilisation. Growth performance was examined in terms of live weight gain (LWG), feed conversion ratio (FCR), specific growth rate (SGR%), protein efficiency ratio (PER), feed efficiency ratio (FER), apparent net protein utilisation (ANPU), energy retention (ER), survival rate and mean weight gain which were calculated according to Prabu et al (2018).…”
Section: Sampling and Growth Performancementioning
confidence: 99%